Does Leadership Style Matter? Moderating Support–Performance Link in Organizations - Maulina, Devy Senza; Taufik, E. Rahmat; Kambara, Roni (The Graduate School of Sahid University, 2025)
This study examines how leadership style moderates the influence of perceived organizational support on employee performance at the UPTD Pengelolaan Jalan dan Jembatan Lebak, Dinas PUPR Provinsi Banten. The decline in employee performance caused by the lack of organizational support perceived by employees needs to be analyzed in terms of the role of the applied leadership style. The method used in this study is a quantitative approach with a survey method involving 93 employees and a saturated sampling technique. The data analysis technique used Structural Equation Modeling (SEM) with the help of SmartPLS version 4 software. The research results show that organizational support perception and leadership style have a positive and significant impact on employee performance. However, leadership style does not have a significant effect and does not moderate the relationship between organizational support perception and performance. The results show that effective leadership style does not strengthen the perception of organizational support. Therefore, organizations should focus on enhancing the perception of organizational support in addition to developing effective leadership styles.